Analisis dan Evaluasi Pengerjaan Soal TOEFL “Structure and Written Expression” - Muhammad Syar’i Ramadhoni; Helmi; Wahdinah; Meilinda Salsabila Mawaddah; Muhammad Indra Saputra (Educational Journal, 2025)
This study aims to analyze and evaluate the process and results of completing the TOEFL (Test of English as a Foreign Language) items in the Structure and Written Expression section. The primary focus is to identify the types of errors most frequently made by test-takers, the patterns of difficulties encountered, and the factors influencing their performance in this section.The research employed a mixed-methods approach, involving a quantitative analysis of test answer data and an in-depth qualitative analysis. The qualitative analysis was conducted through structured interviews to directly explore test-takers' thoughts, completion strategies, and perceptions of difficulty. Additionally, observation of the test-taking process and document analysis of the test results were performed to complement the data. Quantitative analysis results indicate that participants predominantly make errors on specific topics, such as subject-verb agreement and parallel sentence structure. Meanwhile, the qualitative analysis from the interviews reveals that a lack of deep understanding of formal grammar and time constraints are significant obstacles affecting their performance. This evaluation concludes that a learning strategy more focused on syntactic rules and academic writing principles is necessary to enhance the participants' competence in the TOEFL Structure and Written Expression section. The findings of this research are expected to provide practical input for educators and test material developers.